Strategic decision-making under ambiguity: a new problem space and a proposed optimization approach - Richard J. Arend (Business Research, 2020)
The existence of ambiguity presents a challenge to decision-makers as it eliminates the ability to apply standard optimization approaches, such as those based on calculating the objective expected values of alternative actions. In reality, ambiguity arises in most strategically important decisions in some form because of the genuine limits on the decision-maker's rationality and on the information available about the alternatives and the future. To address that reality, we define such problems as strategic decision-making under ambiguity where choices over resource investments must be made in competitive environments where possible outcomes and their payoffs are known ex ante, but the probabilities of such outcomes are unknowable ex ante. We outline a multi-step, logical approach for addressing such problems in theory with the goal of providing an improved basis for practical decisions that should increase organizational performance.
Keywords: B21; D81; G11; M55; 650; Ambiguity; Strategic decision-making; Efficient frontier Managerial incentives